Insulin-like growth factor 1 receptor knockout in mice leads to altered glucose–insulin homeostasis and increased endothelial nitric oxide production. (22nd September 2015) - Abbas, A; Imrie, H; Rajwani, A; Viswambharan, H; Cubbon, RM; Kahn, MB; Gage, M; Wheatcroft, SB; Grant, PJ; Kearney, MT
Abstract : Introduction: Insulin-like growth factor 1 (IGF-1), acting via similar signalling pathways to insulin, enhances glucose uptake and nitric oxide (NO) production. Several studies have demonstrated an inverse relationship between IGF-1 bioactivity and cardiovascular disease. We assessed the hypothesis that a potential mechanism for these findings may be the modulation of endothelial NO bioavailability by IGF-1. Methods: Metabolic tolerance tests were performed on mice, heterozygous for knockout of the IGF-1 receptor (IGF1RKO), and their wild-type littermates (WT). An ex-vivo assessment of vascular function was performed using thoracic aortic rings in an organ bath. Results: IGF1RKO mice had higher random blood glucose measurements than age-matched WT siblings (9.7 mmol/l vs 8.9 mmol/l, respectively, n = 20, p = 0.03). Glucose tolerance tests revealed impaired glucose handling in IGF1RKO mice compared with WT (mean area under the concentration time curve (AUC) IGF1RKO mice 1086 ± 26.82 (mmol/l) minutes, mean AUC WT mice 950.5 ± 22.5 (mmol/l) minutes, n = 5, p = 0.005). Insulin tolerance tests revealed that IGF1RKO mice were more insulin sensitive than controls (mean AUC IGF1RKO 552.2 ± 25.18 (mmol/l) minutes, n = 10; mean AUC for WT 651.4 ± 22.26 (mmol/l) minutes, n = 11, p = 0.008). Aortic rings from IGF1RKO mice were hypocontractile to phenylepherine compared with those from WT (mean Emax IGF1RKO mice 0.60 ± 0.05 g, n = 11 vs mean Emax for WT mice 0.79 ± 0.06 g, n = 10, p = 0.03). Addition of the NO synthase inhibitor, NG-monomethyl-l -arginine (l -NMMA), led to a 65.40 ± 13.40% (n = 9) increase in mean Emax in IGF1RKO mice compared with an 15.78 ± 12.00% (n = 9) increase in WT mice (p = 0.01). In addition, IGF1RKO aortic rings were resistant to IGF-1 exposure compared with WT aortic rings (percentage change in mean Emax for IGF1RKO mice of 32.80 ± 11.01%, n = 9 vs 66.28 ± 10.60% in WT mice, n = 8, p = 0.05), but maintained sensitivity to insulin. Conclusion: IGF1RKO mice have impaired whole-body glucose handling, enhanced insulin sensitivity and increased basal NO production in the vasculature. These data raise the possibility that reduced IGF-1 receptor action in the endothelium may have a favourable effect on NO bioavailability, possibly by a novel interaction with insulin signalling.